Community-based monitoring of Indigenous food security in a changing c limate: Global trends and future directions - Lam, Steven; Dodd, Warren; Skinner, Kelly; Papadopoulos, Andrew; Zivot, Chloe; Ford, James; Garcia, Patricia J.; Team, IHACC Research; Harper, Sherilee L. (Environmental Research Letters, 2019)
Climate change is expected to exacerbate existing food security challe nges, especially in Indigenous communities worldwide. Community-based monitoring is considered a promising strategy to improve monitoring of , and local adaptation to climatic and environmental change. Yet, it i s unclear how this approach can be applied in food security or Indigen ous contexts. The objectives of this paper are to: 1) review and synth esize the published literature on community-based monitoring of Indige nous food security; and, 2) identify gaps and trends in these monitori ng efforts in the context of climate change. Using a systematic search and screening process, we identified 86 published articles. To be inc luded, articles had to be published in a journal, describe a community -based monitoring system, describe any aspect of food security, and ex plicitly mention an Indigenous community. Relevant articles were thema tically analyzed to characterize elements of community-based monitorin g in the context of climate change. Results show that the number of ar ticles published over time was steady and increased more than two-fold within the last five years. The reviewed articles reported on monitor ing mainly in North America (37%) and South America (28%). In general, monitoring was either collaborative with local communities (51%) or e xternally-driven (37%), and focused primarily on tracking wildlife (29 %), followed by natural resources (16%), environmental change (15%), f isheries (13%), climate change (9%), or some combination of these topi cs (18%). This review provides an evidence-base on the uses, character istics, and opportunities of community-based monitoring, to guide futu re food security monitoring efforts in the context of climate change.